Analytical Study of Consumer Buying Behavior Towards Online Food Delivery Channels - Menghani, Kiran; Mishra, Kashinath (SFIMAR Research Review, 2018)
With the growth in ecommerce and its resultant revolution in the economy, the dimensions and nature of online trade and business have changed and increased by leaps and bounds in the present time. The present scenario reflects the adoption of online platforms for all the core activities of the business. The quick service restaurants were mainly responsible for the adoption of online food order system and as a consequence, the larger section of food business which were facing limitations in dispatching the delivery, this shortcoming became the opportunity for online food delivery companies like swiggy and zomato and they started practice of delivering food by connecting the large range of restaurants which lacked the delivery wing and the customer who want to order food anytime, anywhere and from any place. The new concept ATF i.e. Any time food from anywhere came into operation as online operations with respect to order placing has begun. The present study highlights the buying behavior and usage rate of food after the use of online order system and also examine the perception of customers towards it.